Validation of verbal autopsy and nasopharyngeal swab collection for the investigation of deaths at home during the COVID-19 pandemics in Brazil - de Souza, Pedro Mansueto Melo; Gerson, Gunter; Dias, Josebson Silva; de Melo, Deborah Nunes; de Souza, Sarlene Gomes; Ruiz, Erasmo Miessa; Fernandes Tavora, Fabio Rocha; Cavalcanti, Luciano Pamplona de Góes (PLOS Neglected Tropical Diseases, 2020)
null